"MRI CHARACTERISTICS OF PATIENTS WITH NON-FUNCTIONAL PITUITARY MACROADENOMAS WITH SECONDARY EMPTY SELLA SYNDROME DEPENDING ON THE TREATMENT RECEIVED" - Kholikova A.O; Abidova D.Kh (Western European Studies, 2024)
The purpose of the study was to study the MRI characteristics of patients with non-functional pituitary macroadenomas (NFPA) with secondary empty sella syndrome (SEES)_ depending on the treatment received Material and research methods. A total of 35 patients with macro-NfPA and secondary SEES who applied to the outpatient clinic in 2023 were examined. Of these, 15 (42.9%) were men, 20 (57.1%) were women
Keywords: NFPAs; MRI of the pituitary gland; secondary empty sella syndrome